Aphasia as the initial manifestation of herpes encephalitis - Muhammad Shahzad; Asma Ghafoor; Humaira Jurair (Wolters Kluwer Medknow Publications, 2022)
Pediatric acquired aphasia is an uncommon presenting complaint in children. Because of many etiologies that may prove fatal, it is essential to take immediate essential steps for diagnoses and treatment. We are presenting a 9-year-old child who was conscious, alert and did not have any other systemic findings at presentation. After initial and then more extensive workup, he was diagnosed with herpes encephalitis. Acyclovir has been started as empirical antiviral therapy. In the course of disease, he developed status epilepticus that was controlled with multi anti-epileptic drugs. Intravenous acyclovir continued for 21 days, and anti-epilepticus medicines were given at discharge.